Pengaruh Asimetri Informasi Pada Manajemen Laba Dengan Corporate Governance Sebagai Variabel Moderasi - Septiadi, Pande Putu Surya; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
With the information asymmetry, management of companies tend to present information that is not true. The purpose of this study is to determine the effect of information asymmetry on earnings management and the impact of interaction between corporate governance mechanisms to information  asymmetry on earnings management. This study uses a modified jones model to calculate discretionary accruals which become a proxy for earnings management. For corporate governance mechanism is proxied by the composition of the board of directors, board size, the size of the audit committee, and managerial ownership. The sample of this study is a company registered in the Business Index 27 in the Indonesia Stock Exchange. Regression analysis used is the interaction. Based on the discussion of research results prove that the positive effect of information asymmetry on earnings management. This study also indicate that the composition of the board of directors and the size of the audit committee able to moderate (weaken) the relationship of information asymmetry on earnings management, while other proxies such as board size and managerial ownership is not able to moderate the relationship information asymmetry on earnings mana . gement.
Keywords: earnings management, discretionary accruals, information asymmetry, corporate governance mechanism